Doing political science and international relations : theories in action - Savigny, Heather; Marsden, Lee. (New York : Palgrave MacMillan, 2011)
'This book provides a new type of introduction to politics and international relations that examines how, why, and what we study. Systematic and accessible in its approach, it introduces the analytical toolkits needed to study politics and international relations. The book takes a fully integrated approach to domestic and global politics, incorporating real-world case studies throughout'--
Machine generated contents note: -- Introduction -- Themes and Issues in Political Science & International Relations -- Power -- The State -- Policy -- Institutions -- Representation and Participation -- Media -- Security -- International/Political Economy -- The Environment -- Globalisation -- Doing Your Own Political Science and International Relations.
Includes bibliographical references (p. 286-306) and index.
Keywords: Political science -- Methodology; International relations -- Methodology; Political science -- Study and teaching; International relations -- Study and teaching; POLITICAL SCIENCE / Globalization; POLITICAL SCIENCE / Government / General; POLITICAL SCIENCE / Political Ideologies / General; POLITICAL SCIENCE / International Relations / General